The Frequency, Severity, and Risk Factors of Hickman CatheterRelated Complications in Pediatric Cancer Patients: A Single-Center Experience from Bosnia and Herzegovina - Zlatan Zvizdic; Emin Zaimovic; Emir Milisic; Asmir Jonuzi; Una Glamoclija; Semir Vranic (Turkish Archives of Pediatrics)
Objective: This study aimed to identify the frequency, severity, and risk factors associated with Hickman catheter-related complications in children with hemato-oncological malignancies at the largest pediatric tertiary care unit in Bosnia and Herzegovina.